Resource management for QoS support in cellular - Wei Song (IEEE Network : the magazine of global information exchange)
To provide mobile users with seamless Internet access anywhere and anytime/ there is a strong demand for interworking mechanisms between cellular networks and wireless local area networks in the next-generation all-IP wireless networks. In this article we focus on resource management and call admission control for QoS support in cellular/WLAN interworking. In specific, a DiffServ interworking architecture with loose coupling is presented. Resource allocation in the interworking environment is investigated/ taking into account the network characteristics, vertical handoff, user mobility, and service types. An effective call admission control strategy with service differentiation is proposed for QoS provisioning and efficient resource utilization. Numerical results demonstrate the effectiveness of the proposed call admission control scheme.